ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI INTERVENING (Studi Kasus pada Lunpia Mbak Lien Semarang) - Pradhana, Adhika; Sugiarto, Johanes (Faculty of Economics and Business Diponegoro University, 2015)
Many businesses today's culinary cause business competition is getting tougher. Therefore, each company is required to be able to make the right business strategy in order not to lose competitiveness, so that customers remain satisfied and can improve the customer loyalty.This study aims to describe the influence of product quality and service quality in influencing customer satisfaction, in order to increase customer loyalty in Lunpia Mbak Lien Semarang.The study was conducted by taking samples using purposive sampling technique, which has ever visited and bought lunpia in Lunpia Mbak Lien Semarang. The collection of data obtained from 150 customers Lunpia Mbak Lien Semarang by questionnaire consisting of open and closed questions.Respondents' answers to open-ended questions were analyzed qualitatively, and answers to the closed questions were analyzed with methods (Structural Equation Modeling) SEM using AMOS program assistance 22 for Windows.The analysis showed that the quality of the product has a positive and significant impact on customer satisfaction with the regression value of 0.30, and the quality of the product has a positive and significant effect on customer loyalty with regression value of 0.24.Quality of service has a positive and significant impact on customer satisfaction with the regression value of 0.58, and the quality of service has a positive and significant effect on customer loyalty with regression value of 0.30.And customer satisfaction has a positive and significant impact on customer loyalty with regression value of 0.32 at Lunpia Mbak Lien Semarang.